Factors affecting caregivers’ HPV vaccination decisions for adolescent girls: A secondary analysis of a Chinese RCT - Ying Yang; Yajiao Lu; Yifan Li; Chuanyu Qin; Yu He; Wenfeng Gong; Shenglan Tang; Dan Wu; Jing Li (PLoS ONE, 2025)
Background Despite the HPV vaccine’s effectiveness against cervical cancer, uptake among adolescent girls in China remains low, with caregivers playing a crucial role in vaccination decisions. This study investigates factors influencing caregivers’ action to vaccinate their adolescent daughters. Methods Pay-it-forward is a novel model that motivates participants in adopting healthy behaviors and making community contributions. In this study, it offers an individual a free shot of HPV vaccine and then asks whether they would like to donate to support another person to get the same vaccination. This study was embedded in a two-arm randomized controlled trial in China. Potential associated factors were identified based on Anderson’s Health Service Utilization Behavioral Model and analyzed through univariate and multivariate binary logistic regression. Caregivers’ information, knowledge, attitudes, vaccine confidence, hesitancy, and willingness to vaccinate were collected through online questionnaires. The endpoint was the receipt of the first dose HPV vaccine following an intervention or no intervention (pay-it-forward vs. standard-of-care), which was obtained from an electronic vaccination registry system. Results Among 321 caregivers, 25.9% of their daughters received the HPV vaccine, with 34.2% in the pay-it-forward group and 17.5% in the standard-of-care group. Daughters of caregivers who were previously unaware of the HPV vaccine were three times more likely to be vaccinated (OR=3.01,95%CI:1.27–7.14). Caregivers who did not intend to delay vaccination had daughters with eight times higher vaccination uptake (OR=8.26,95%CI:4.36–15.67). Participation in the “pay-it-forward” intervention increased vaccination rates by more than twofold (OR=2.22,95%CI:1.19–4.15). Daughters of unemployed or retired caregivers had nearly four times higher vaccination rates compared to those whose caregivers were employed (OR=3.97,95%CI:1.81–8.72). Prior refusal of the vaccine by caregivers was associated with an 80% reduction in vaccination uptake among daughters (OR=0.23,95%CI:0.06–0.81). Conclusion The pay-it-forward intervention, caregivers’ knowledge, intention to delay vaccination, occupation, and prior vaccine refusal significantly influence HPV vaccine uptake among adolescent girls in China. Tailored health education, financial support, and community involvement are essential to encourage HPV vaccination among adolescent girls in China.